Harnessing the Natural Biology of Adeno-Associated Virus to Enhance the Efficacy of Cancer Gene Therapy - Bower, Jacquelyn J. (Viruses, 2021)
Adeno-associated virus (AAV) was first characterized as small “defective” contaminant particles in a simian adenovirus preparation in 1965. Since then, a recombinant platform of AAV (rAAV) has become one of the leading candidates for gene therapy applications resulting in two FDA-approved treatments for rare monogenic diseases and many more currently in various phases of the pharmaceutical development pipeline. Herein, we summarize rAAV approaches for the treatment of diverse types of cancers and highlight the natural anti-oncogenic effects of wild-type AAV (wtAAV), including interactions with the cellular host machinery, that are of relevance to enhance current treatment strategies for cancer.